THE EXAMINATION OF THE BASIC SKILL LEVELS OF THE STUDENTS' IN ACCORDANCE WITH THE PERCEPTIONS OF TEACHERS, PARENTS AND STUDENTS - Hotaman, Davut (ESKISEHIR OSMANGAZI UNIV, FAC EDUCATION, 2008)
In this research, the level of possession of the students' basic skills that are anticipated to be cultivated into student by the new elementary education program were evaluated in terms of the perceptions of teachers, parents and students. For the sample groups of this research, the 4th and 5th grade students (527) from 16 schools, the parents (527) of these students and the teachers (148) of the 4th and 5th grade in the districts of Istanbul (Avcilar, Bakirkoy and Sisli), which is the largest city of Turkey, in the academic year 2006-2007, were chosen. The data collected via the research were analyzed by SPSS 15.0 package and the perception points of each 4th and 5th grade students towards the basic skills were assessed. Whether the total perception points of the groups differentiated from one another in each of the sub-dimensions was tested by MANOVA, for each sub-dimension, it was tested by ANOVA; and, to determine the source of the differences, Games-Howell Test was used. The significance level was taken as 0.05 in this research. Through the analyses it was determined that the teachers', parents' and students' perceptions towards the 4th and 5th grade students' possession of the basic skills and all sub-dimensions have a significant difference.
Keywords: critical and creative thinking; communication; researching-interrogating; problem solving and enterprising/assertiveness; Education & Educational Research